Analisis Kualitas Udara Nitrogen Dioksida (No2) di Jalan Haji Agus Salim - Ely Selyna; Peppy Herawati; Asih Suzana (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
The Siginjai Keris Monument stands as one of the most distinctive landmarks of Jambi City, simultaneously serving as a prominent tourist destination nestled within the administrative precinct along Jl. H. Agus Salim. The substantial influx of visitors alongside concentrated office activities has progressively amplified vehicular mobility in the vicinity, consequently elevating ambient air pollutant levels, most notably nitrogen dioxide (NO2). This investigation was undertaken to quantify the concentration and delineate the dispersal pattern of NO2 along Jl. H. Agus Salim employing the AERMOD modelling approach, within a quantitative descriptive research framework. Empirical findings revealed that NO2 concentrations remained beneath the permissible threshold of 200 µg/m³ stipulated under Government Regulation Number 22 of 2021. AERMOD dispersion modelling further disclosed a maximum NO2 emission concentration of 25.6 µg/m³ in the ambient atmosphere, whilst the minimum recorded concentration reached 3.4 µg/m³, both of which remained comfortably within the prescribed quality benchmarks.